Unpacking the Blue Box: structure, control and education in policing. (21st October 2022) - Cockcroft, Tom; Hallenberg, Katja M.
ABSTRACT : Research addressing the relationship between Higher Education (HE) and police officers tends to fall into one of three camps. First, that which explores the relationship between police institutions and academic institutions, second, those which explore the appropriateness of the HE setting for the delivery of police-specific knowledge, and, finally, research which investigates the impact of police higher education engagement upon police officer attributes and practice (Brown. 2018. Do graduate police officers make a difference to policing? Results of an integrative literature review. Policing: a journal of policy and practice, policing, 1–22. doi:10.1093/police/pay075 ). Thus far, little research has discussed the impact HE has on the relationship between officers and the police organisation. This research, derived from interviews with 31 police officers who undertook in-service degrees, explores police officers' engagement with HE study and the consequent changes to their perception of their relationship with the profession. This is contrasted with the relatively unchanged structural and cultural expectations the organisation places on officers regardless of their newly acquired graduate status as reported in the extant literature (Hallenberg and Cockcroft. 2017. From indifference to hostility: police officers, organisational responses and the symbolic value of 'in-service' higher education in policing. Policing: a journal of policy and practice, 11 (3), 273–288). The discrepancy can be explained through the recent scholarship on public sector isomorphism and the police's transformation into a hybrid organisation (Noordegraaf. 2015. Hybrid professionalism and beyond: new forms of public professionalism in changing organizational and societal contexts. Journal of professions and organization, 2, 187–206), as well as the competing knowledge paradigms within policing (Williams and Cockcroft. 2018. Knowledge wars: professionalisation, organisational justice and competing knowledge paradigms in British policing. In : L. Huey, and R Mitchell, eds. Evidence-based policing: an introduction . Bristol: Policy Press, 131–141). Importantly, however, the current paper takes this discussion deeper. It argues that the police's unique role in serving not just the public but also state interests inevitably shapes and constrains the process of professionalisation, the relationship between the police and HE, and officers' ability to use knowledge and skills gained through HE study.